THEORETICAL-LEGAL DESCRIPTION OF LEGAL PRECEDENTS AS A SOURCE OF LAW - Eshturdiyeva Farangiz Bakhodirovna (PEDAGOGS, 2024)
Forms of expression and strengthening of legal norms among the general theoretical problems of legal science are determined as a source of law in formal-legal content. The source of law is known as a basic concept that is important in demonstrating consistency and precision in the expression of legal norms. This understanding provides an opportunity to understand the content of legal norms through social factors, forces that directly create law, and sources of information about law. Although we do not include precedent as a source of law in our national legal system, theoretically, the issues of study show that there is a significant gap in the theory of law, the need to pay attention to precedents as a source of law has not been sufficiently studied. It is no exaggeration to say that this article theoretically bases the concept of legal precedent, analyzes the opinions of scientists, and contributes to the theory of law in a small way.